Wpływ zagęszczenia sadzonek buka zwyczajnego w pojemnikach na jego cechy morfologiczne - Wrzesiński, Piotr (Leśne Prace Badawcze, 2015)
This study examines the influence on growth parameters, in particular the morphological features of the root system, of 1-year-old European beech seedlings cultivated in containers with two different densities. The experiment was conducted in the container nursery in Skierdy (Forest District of Jabłonna) in spring 2011. After 10 months of cultivation in Hiko polyethylene containers, above- and below-ground parts of the seedlings were measured. The measurements of the root system were conducted with a scanner and the WinRHIZO software. No influence due to the seedling density on either shoot height or thickness was observed, but instead the research showed that different seedling densities affected the development of root systems. The mean root thickness and dry mass of the European beech seedlings were significantly higher at the lower density. The influence of seedling density on the development of root mass deserves special attention as it is the most important factor affecting future growth of the seedlings during cultivation. This tendency also suggests that the amount of nutrients allocated to shoot development may be higher in order to improve the efficiency of photosynthesis. At both densities, differences in biomass accumulation affected the root-toshoot ratio. In seedlings cultivated at the lower density, the increased dry root matter of the seedlings resulted in a significant increase in the root-to-shoot ratio. This may cause a potential growth advantage of these seedlings after they are planted and may thus result in a more productive cultivation.